ANALISIS PENDEKATAN UI/UX PERANCANGAN APLIKASI ANDROID PADA TOKO JHON - Rasmila, Rasmila; Mardiyansya, Yogi; Udariyansyah, Devi; Sauda, Siti (J-Icon : Jurnal Komputer dan Informatika, 2023)
Jhon's Shop is a shop that sells various kinds of necessities for other smaller shops. Along with its development, Toko Jhon wants to add digital marketing methods to its products. The aim of this research is to design a user interface and user experience (UI/UX) for the Toko Jhon mobile application by applying the user-centered design method with four stages namely, specifying the context of use, specifying user requirements, designing solutions, and evaluating against requirements with heuristic evaluations to carry out the evaluation. User interface and user experience are important factors to ensure that users are comfortable when using the application. In the Design Solutions Stage, the author carries out low-fidelity and high-fidelity designs with the help of the Figma application. After the design is formed, an evaluation is carried out using heuristics, assisted by an evaluator. The results of calculations using the heuristic evaluation method showed that 18 statements were included in the Good and Very Good qualifications, and there were 2 statements included in the Fairly Good and Not Good qualifications, which were found in the Heuristics Help and Documentation aspect with recommendations for improvement namely, adding a help button and a contact admin feature. After improvements have been made, the UI/UX design is ready to be implemented in the application prototype.